2018
DOI: 10.1590/1676-0611-bn-2017-0322
|View full text |Cite
|
Sign up to set email alerts
|

Anuran amphibians in state of Paraná, southern Brazil

Abstract: The state of Paraná, located in southern Brazil, was originally covered almost entirely by the Atlantic Forest biome, with some areas of Cerrado savanna. In the present day, little of this natural vegetation remains, mostly remnants of Atlantic Forest located in the coastal zone. While some data are available on the anurans of the state of Paraná, no complete list has yet been published, which may hamper the understanding of its potential anuran diversity and limit the development of adequate conservation meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…1" from RPPNSM, municipality of Guaraqueçaba, Paraná, identified as B. sulfuratus (Table 1) based on their call structure, with few notes and only isolated notes (MHNCI 133; Table 2). On the basis of this record, we reverted in favor of B. sulfuratus all other records of B. hermogenesi at RPPNSM (Pereira et al, 2010;Santos-Pereira et al, 2011Santos-Pereira, Pombal & Rocha, 2018;Leivas et al, 2018; Table 1). Some previous studies reporting "Brachycephalus hermogenesi" (Giaretta & Sawaya, 1998;Dixo & Verdade, 2006;Verdade et al, 2008;Condez, Sawaya & Dixo, 2009;Verdade, Rodrigues & Pavan, 2009) from São Paulo do not provide enough morphological evidence or other details to allow us to reassess their original identification by us (Table 1; Fig.…”
Section: Geographical Occurrence Records Of Brachycephalus Sulfuratus and B Hermogenesimentioning
confidence: 57%
“…1" from RPPNSM, municipality of Guaraqueçaba, Paraná, identified as B. sulfuratus (Table 1) based on their call structure, with few notes and only isolated notes (MHNCI 133; Table 2). On the basis of this record, we reverted in favor of B. sulfuratus all other records of B. hermogenesi at RPPNSM (Pereira et al, 2010;Santos-Pereira et al, 2011Santos-Pereira, Pombal & Rocha, 2018;Leivas et al, 2018; Table 1). Some previous studies reporting "Brachycephalus hermogenesi" (Giaretta & Sawaya, 1998;Dixo & Verdade, 2006;Verdade et al, 2008;Condez, Sawaya & Dixo, 2009;Verdade, Rodrigues & Pavan, 2009) from São Paulo do not provide enough morphological evidence or other details to allow us to reassess their original identification by us (Table 1; Fig.…”
Section: Geographical Occurrence Records Of Brachycephalus Sulfuratus and B Hermogenesimentioning
confidence: 57%
“…Therefore, the species richness of anurans recorded at RBV in the present study represents ca. 13% of the species occurrence for the state of Paraná (137 total; Santos-Pereira et al 2018) and ca. 44% of the species occurrence for the west of Paraná (36 total; Leivas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The other three species, Cycloramphus eleutherodactylus, Vitreorana eurygnatha, and V. uranoscopa, are listed only at the state level (Bergallo et al 2000), as Presumably Threatened, and only C. eleutherodactylus is listed by the IUCN (2020), as Data Deficient. Cycloramphus eleutherodactylus is known to occur in the Brazilian states of Paraná, São Paulo, Rio de Janeiro, and Minas Gerais (Rossa-Feres et al 2017, Santos-Pereira et al 2018, although some studies have reported its disappearance by the beginning of the 20th century (Izecksohn & Carvalho-e-Silva 2001, Eterovick et al 2005. We did not collect C. eleutherodactylus during fieldwork and it has not been found at PNT since 1972 (Matos 2011).…”
Section: Conservation: Endemism Threat Status and Exotic Speciesmentioning
confidence: 94%